Barriers to Applying Value Management in the Vietnamese Construction Industry - Soo , Yong Kim; Yeon , San Lee; Viet , Thanh Nguyen; Van , Truong Luu (Penerbit Universiti Sains Malaysia, 2016)
The value management (VM) approach often faces many barriers when applied in the Vietnamese construction industry, as well as in many other developing countries. Most of the related past works identify an insufficient number of factors that hinder the application of VM. This study identified 18 factors hindering the application of VM in the construction industry. To gather views from industrial practitioners with many years of experience in construction projects, this study administered questionnaire surveys. The findings revealed that the four greatest obstacles to the application of VM were the lack of VM experts, the lack of knowledge about VM, the lack of local VM guidelines, as well as technical norms and standards, and the lack of investments, support policies and human resources to conduct VM in construction companies. Additionally, the factor analysis method was applied to investigate the correlation effects of the hindrance factors, which resulted in four core components representing the hindrance factors, namely, lack of qualified personnel to implement VM, inherent difficulties with VM workshops, lack of awareness of VM, and lack of VM application documents. The study contributes to the body of knowledge relating to the application of VM in the construction industry. The findings can be generalised to many developing countries, as they face similar problems in terms of promoting the application of VM in the construction industry